1995
DOI: 10.1016/0092-8674(95)90425-5
|View full text |Cite
|
Sign up to set email alerts
|

In vitro guidance of retinal ganglion cell axons by RAGS, a 25 kDa tectal protein related to ligands for Eph receptor tyrosine kinases

Abstract: The results of previous in vitro experiments indicate that a glycosylphosphatidylinositol (GPI)-anchored protein may play an important role in the guidance of temporal retinal axons during the formation of the topographically ordered retinotectal projection. We have purified and cloned a GPI-anchored, 25 kDa glycoprotein that is a good candidate for a molecule involved in this process. During the time of innervation by retinal ganglion cells, this protein is gradedly expressed in the posterior part of the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
614
4
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 811 publications
(649 citation statements)
references
References 55 publications
28
614
4
3
Order By: Relevance
“…Moreover, the presence of potential ephrinA5 receptors such as EphA3 [40], EphB2 [41], EphA5 [35,42,43], EphA7 and EphA4 [35] has been also described in the mitral cells during embryogenesis. This suggests that ephrinA5 and its receptors are not expressed in complementary gradient as it has been described for other systems such as the retinotectal one [8,44]. Instead, we showed that ephrinA5 is uniformly expressed in this structure as for its receptors [40-42,35,20].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Moreover, the presence of potential ephrinA5 receptors such as EphA3 [40], EphB2 [41], EphA5 [35,42,43], EphA7 and EphA4 [35] has been also described in the mitral cells during embryogenesis. This suggests that ephrinA5 and its receptors are not expressed in complementary gradient as it has been described for other systems such as the retinotectal one [8,44]. Instead, we showed that ephrinA5 is uniformly expressed in this structure as for its receptors [40-42,35,20].…”
Section: Discussionsupporting
confidence: 71%
“…EphrinA5 RNA is known to be expressed in a caudal (high) to rostral (low) gradient in the mouse superior colliculus [44,50,55]. This gradient is thought to be at the basis of the chemorepellent action of ephrinA5 on retinal ganglion cell's axons arising from the nasal part of the retina [50].…”
Section: Discussionmentioning
confidence: 99%
“…Elf-1/Cek7-L is highly expressed at the midbrain tectum in a decreasing caudal-rostral gradient (Cheng and Flanagan, 1994;Cheng et al, 1995). AL-1/RAGS is also highly expressed in the caudal tectum (Drescher et al, 1995). Ehk1-L/E¯-2/Lerk3 is highly expressed in the brain although its speci®c localization in the brain has not yet been reported (Davis et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used degenerate oligonucleotides designed from conserved regions of the Eph family ligands to amplify related sequences from mouse brain cDNA since the expression of the Eek receptor is brain-speci®c. Three known ligands, Elf-1/Cek7-L (Cheng and Flanagan, 1994;Shao et al, 1995), Ehk1-L/E¯-2/Lerk3 (Davis et al, 1994) and AL-1/RAGS (Winslow et al, 1995;Drescher et al, 1995), were ampli®ed and subsequently their full-length cDNAs were cloned from a mouse brain cDNA library. To investigate whether these ligands can bind to the Eek receptor, we constructed expression vectors containing the entire coding sequence of the ligands, except for the hydrophobic sequence of each ligands fused to the Fc portion of human immunoglobulin G1 (Figure 5a).…”
Section: Three DI Erent Gpi-linked Eph Family Ligands Can Bind To Thementioning
confidence: 99%
See 1 more Smart Citation